2020
DOI: 10.3389/fnagi.2020.00101
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium and Cognitive Function Among Qatari Adults

Abstract: Background: Previous studies found that low blood magnesium increases the risk of several diseases such as cardiovascular diseases (CVD), diabetes, and hypertension. These ailments are associated with declined cognitive function.Objective: We aimed to examine the association between serum magnesium and cognitive function among Qatari adults. In addition, we assessed the interaction relation between low serum magnesium, hypertension, and diabetes in relation to cognitive function.Method: Data from 1,000 Qatari … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
4
16
0
Order By: Relevance
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our study were consistent with the results of most of the previous studies in both humans and animals [7][8][9][10][11][12][13][14][15][16][23][24][25][26]. A cross-sectional study conducted in Spain on 447 participants found that increased intake of Mediterranean-diet components including walnuts is linked to better cognitive function and increased working memory in elderly at high cardiovascular risk [27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concurrently, hypokalemic metabolic alkalosis, hypocalciuria, hypomagnesemia and activated RAAS with secondary hyperaldosteronism do not have strong neurological effects in these patients. However, magnesium deficiency might have cognitive effects [ 25 ]. It is worth noting that GS patients are often polysymptomatic (e.g.…”
Section: Introductionmentioning
confidence: 99%